Optimizing the performance of microbial fuel cells fed a combination of different synthetic organic fractions in municipal solid waste. (March 2016) - Pendyala, Brahmaiah; Chaganti, Subba Rao; Lalman, Jerald A.; Heath, Daniel D.
Graphical abstract: Highlights: Municipal solid waste is a potential feedstock for MFCs to produce electricity. Microbial composition of the anode biofilm was a function of the feed composition. Low protein and high carbohydrate content favored maximum COD removal and CE. Abstract: The objective of this study was to establish the impact of different steam exploded organic fractions in municipal solid waste (MSW) on electricity production using microbial fuel cells (MFCs). In particular, the influence of individual steam exploded liquefied waste components (food waste (FW), paper–cardboard waste (PCW) and garden waste (GW)) and their blends on chemical oxygen demand (COD) removal, columbic efficiency (CE) and microbial diversity was examined using a mixture design. Maximum power densities from 0.56 to 0.83 W m −2 were observed for MFCs fed with different feedstocks. The maximum COD removed and minimum CE were observed for a GW feed. However, a reverse trend (minimum COD removed and maximum CE) was observed for the FW feed. A maximum COD removal (78%) accompanied with a maximum CE (24%) was observed for a combined feed of FW, PCW plus GW in a 1:1:1 ratio. Lactate, the major byproduct detected, was unutilized by the anodic biofilm community. The organic fraction of municipal solid waste (OFMSW) could serve as a potential feedstock for electricity generation in MFCs; however, elevated protein levels will lead to reduced COD removal. The microbial communities in cultures fed FW and PCW was highly diversified; however, the communities in cultures fed FW or a feed mixture containing high FW levels were similar and dominated by Bacteroidetes and β-proteobacteria .